2019
DOI: 10.21470/1678-9741-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lung Expansion Therapy Using Positive End-Expiratory Pressure in Mechanically Ventilated Patients Submitted to Coronary Artery Bypass Grafting

Abstract: ObjectiveTo evaluate the impact of different levels of positive end-expiratory pressure (PEEP) on gas exchange in patients undergoing coronary artery bypass grafting (CABG).MethodsA randomized clinical trial was conducted with patients undergoing CABG surgery. Patients were randomized into three groups: Group 10, PEEP of 10 cmH2O; Group 12, PEEP of 12 cmH2O; and Group 15, PEEP of 15 cmH2O. After the randomization, all patients underwent gas analysis at three moments: (1) before lung expansion therapy (LET); (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Meanwhile, the year of publication widely varied across the studies, with 12 of them published before 2000 ( Table 1 ). RoB was high in 18 ( 15 17 , 20 , 23 , 24 , 27 , 28 , 30 32 , 34 – 38 , 40 , 41 ) and low in 10 ( 5 , 10 , 18 , 19 , 21 , 22 , 25 , 26 , 29 , 33 ) trials. The high RoB was attributed to blinding of participants, personnel and outcome assessors ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, the year of publication widely varied across the studies, with 12 of them published before 2000 ( Table 1 ). RoB was high in 18 ( 15 17 , 20 , 23 , 24 , 27 , 28 , 30 32 , 34 – 38 , 40 , 41 ) and low in 10 ( 5 , 10 , 18 , 19 , 21 , 22 , 25 , 26 , 29 , 33 ) trials. The high RoB was attributed to blinding of participants, personnel and outcome assessors ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 95%
“…A total of 11 eligible articles(5,10,16,19,21, 23,25,29,33,35,38), with 1,848 participants, reported duration of mechanical ventilation. Among them, 6 studies(16,19,21, 23,25,29), with 572 patients(16,19,21, 23,25,29). A summary of the RoBs is shown in Figure3while the resulting funnel plot is illustrated inFigure 4. among different PEEP strategies (higher vs. intermediate: MD: 0.02, 95% CI: −0.034, 0.073; intermediate vs. lower: MD: −0.03, 95% CI: −0.078, 0.017; and lower PEEP vs. ZEEP: MD: 0.03, 95% CI: 0.015, 0.046) (Figure 5A).…”
mentioning
confidence: 99%
“…After carefully reading the full text of the remaining 63 articles, we found 39 of them inappropriate for the following reasons: 1) not ICU patients (n = 3); 2) disequilibrium of other ventilation parameters (n = 7); 3) not RCT (n = 3); 4) animal trials (n = 2); 5) receiving different PEEP within single patients (n = 15); 6) including patients with ARDS or age under 18 (n = 2); 7) retrospective studies (n = 4); 8) intraoperative studies (n = 2) and 9) full article unavailable. Therefore, we nally analyzed 24 studies [5,8,[10][11][12][13][14][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Although there was one meta-analysis published in 2016 investigating the possible effect of high PEEP, the quality of evidence was low and insu cient [15] . In our present meta-analysis, we added four recent RCTs [33][34][35] including one largest RCT concerning high PEEP usage in non-ARDS patients [14] . Moreover, given that most of the selected patients underwent operations, especially cardiac ones, we also assessed the impact of high PEEP on postoperative chest-tube drainage and RBC usage, with no signi cant difference found.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Positive end-expiratory pressure has been conducted in a study with mechanically ventilated patients submitted to coronary artery bypass grafting. It has been demonstrated that high levels of positive end-expiratory pressure (15 cmH 2 O) are beneficial for the improvement of gas exchange in those patients [62]. This technique has also been evaluated in patients after upper abdominal surgery, and no significant differences in lung expansion or post-operative pulmonary complications were observed compared with incentive spirometry [63].…”
Section: Techniques For Lung Expansionmentioning
confidence: 99%